Pengaruh Kepemimpinan, Lingkungan Kerja, Beban Kerja dan Stres Kerja Terhadap Kepuasan Kerja Karyawan di PT. Royal Korindah Purbalingga - Aemi Nia Safria; Edi Sumantri; Ady Achadi (Majalah Imiah Manajemen & Bisnis, 2023)
The purpose of this study was to determine the effect of leadership, work environment, workload and work stress on employee job satisfaction at PT. Royal Korinda Purbalingga. The population is production employees of PT. Royal Korinda Purbalingga with a total of 97 respondents using simple random sampling technique. The analytical method used is multiple linear regression analysis. The conclusion for this study is that Leadership, Work Environment, have a positive and significant effect on employee job satisfaction at PT Royal Korindah Purbalingga. While the variable workload and work stress have a negative and significant effect on employee job satisfaction at PT. Royal Korinda Purbalingga. Referring to these conclusions, it can be implied that as an effort to continuously improve employee job satisfaction, the management at PT. Royal Korinda Purbalingga needs to apply the right policies related to leadership, work environment, workload and work stress. Ways that can be done include providing adequate support to co-workers, leaders increasing the ability to listen to ideas or ideas from subordinates, increasing a comfortable and harmonious work environment, paying attention to employee workload so that it is not too heavy according to employee abilities, and not giving work that exceeds the capacity of employees so that they have no difficulty meeting work standards.